2015
DOI: 10.3928/1081597x-20150820-09
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of Planned Versus Achieved Stromal Thickness Reduction in Myopic Femtosecond Laser-assisted LASIK

Abstract: Actual objective stromal thickness reduction following myopic LASIK correlates well with the attempted versus achieved refractive change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
2
11
1
1
Order By: Relevance
“…Contrary to our findings, Kanellopoulos et al 24 reported a lower central ablation efficiency of 97.2% with a similar laser (Wavelight EX500) in myopic LASIK. The difference may be explained by the following: First, Kanellopoulos et al measured the difference between the preoperative and postoperative stromal thicknesses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, Kanellopoulos et al 24 reported a lower central ablation efficiency of 97.2% with a similar laser (Wavelight EX500) in myopic LASIK. The difference may be explained by the following: First, Kanellopoulos et al measured the difference between the preoperative and postoperative stromal thicknesses.…”
Section: Discussioncontrasting
confidence: 99%
“…This could artifactually decrease the measured ablation depth in the study. 24 Second, the ablation efficiency tends to be higher for a deeper ablation (nonlinear effect) due to stromal dehydration. The tissue ablation depth used in our study was deeper than the LASIK stromal ablation depth in the study by Kanellopoulos et al In addition, there was a time interval between the myopic ablation and hyperopic ablation (approximately 50 seconds) in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 35 The variability in the maximum ablated tissue by the excimer laser also constitutes an independent factor. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more complex ablation profiles, such as wavefront, wavefront optimized, or topography guided, complicate the calculation of ablation depth. Consequently, the refractive surgeon relies on the estimated ablation depth provided by the laser machine's software [11] .…”
Section: Discussionmentioning
confidence: 99%